Thermal characterization of carbon nanotube foam using MEMS microhotplates and thermographic analysis. Issue 15 (31st March 2016) - Silvestri, Cinzia; Riccio, Michele; Poelma, René H.; Morana, Bruno; Vollebregt, Sten; Santagata, Fabio; Irace, Andrea; Zhang, Guo Qi; Sarro, Pasqualina M.
Abstract : Lithographically defined carbon nanotube foam structures enhance the surface driven heat transfer mechanisms of microelectronic systems. Abstract : Thermal material properties play a fundamental role in the thermal management of microelectronic systems. The porous nature of carbon nanotube (CNT) arrays results in a very high surface area to volume ratio, which makes the material attractive for surface driven heat transfer mechanisms. Here, we report on the heat transfer performance of lithographically defined micropins made of carbon nanotube (CNT) nanofoam, directly grown on microhotplates (MHPs). The MHP is used as an in situ characterization platform with controllable hot-spot and integrated temperature sensor. Under natural convection, and equivalent power supplied, we measured a significant reduction in hot-spot temperature when augmenting the MHP surface with CNT micropins. In particular, a strong enhancement of convective and radiative heat transfer towards the surrounding environment is recorded, due to the high aspect ratio and the foam-like morphology of the patterned CNTs. By combining electrical characterizations with high-resolution thermographic microscopy analysis, we quantified the heat losses induced by the integrated CNT nanofoams and we found a unique temperature dependency of the equivalent convective heat transfer coefficient, H c . The obtained results with the proposed non-destructive characterization method demonstrate that significant improvements can be achieved in microelectronic thermal management and hierarchical structured porous material characterization.